The extensive geographical range of several species of Teloschistaceae: evidence from Russia. (3rd May 2016) - VONDRÁK, Jan; FROLOV, Ivan; DAVYDOV, Evgeny A.; URBANAVICHENE, Irina; CHESNOKOV, Sergey; ZHDANOV, Ilya; MUCHNIK, Evgenia; KONOREVA, Ludmila; HIMELBRANT, Dimitry; TCHABANENKO, Svetlana
Abstract: The current view of the geographical ranges of lichens is often distorted by overly narrow or overly broad applications of names and by insufficient survey of most regions of the world. Here we present several cases where species of Teloschistaceae formerly thought to be limited to rather small territories in the western or eastern parts of Eurasia are in fact widespread in northern Eurasia. We support our findings with ITS nrDNA data in several new trees showing relationships in the genera Athallia, Calogaya, Caloplaca, Flavoplaca and Gyalolechia . The widespread species have little in common, except that most of them reproduce both sexually and asexually, and we discuss the possible influence of the combined reproduction on geographical range. Calogaya bryochrysion, Calogaya saxicola, Gyalolechia epiphyta and Gyalolechia ussuriensis are new combinations. Calogaya alaskensis is a younger synonym for C. bryochrysion . The generally arctic-alpine Calogaya bryochrysion also occurs on the bark of solitary trees in dry parts of the Altai Mountains. The Australian Flavoplaca cranfieldii is a younger synonym of F. flavocitrina . Gyalolechia epiphyta has been described numerous times, from different regions and substrata, as Caloplaca juniperi, C. laricina, C. tarani, Gyalolechia arizonica and G. juniperina . The name Gyalolechia xanthostigmoidea has recently been used for G. epiphyta, but it represents a distinct taxon. Gyalolechia ussuriensis is closely related to and morphologically indistinguishable from G. persimilis, but they have a different ecology and distribution and we regard them as distinct species. Caloplaca juniperina Tomin is lectotypified.